Generation of antibody-based therapeutics targeting the idiotype of B-cell malignancies. (27th December 2018) - Weiss, Emily; Sarnovsky, Robert; Ho, Mitchell; Arons, Evgeny; Kreitman, Robert; Angelus, Evan; Antignani, Antonella; FitzGerald, David
ABSTRACT: Background: A feature of many B-cell tumors is a surface-expressed immunoglobulin (sIg). The complementarity-determining regions (CDRs) of the sIg, termed the 'idiotype', are unique to each tumor. We report on a phage selection strategy to generate anti-idiotype therapeutics that reacts with sIg CDR3 sequences; the MEC1 B-cell tumor line was used as proof of concept. Methods: To create a mimetic of the MEC1 idiotype, CDR3 sequences from heavy and light chains of the sIg were grafted into a single chain variable fragment (scFv) framework scaffold. Using the Tomlinson I phage library of human scFvs, we enriched for binders to MEC1 CDR3 sequences over unrelated CDR3 sequences. Results: By ELISA we identified 10 binder phages. Of these, five were sequenced, found to be unique and characterized further. By flow cytometry each of the five phages bound to MEC1 cells, albeit with different patterns of reactivity. To establish specificity of binding and utility, the scFv sequences from two of these binders (phages 1 and 7) were converted into antibody-toxin fusion proteins (immunotoxins) and also cloned into a human IgG1 expression vector. Binders 1 and 7 immunotoxins exhibited specific killing of MEC1 cells with little toxicity for non-target B-cell lines. The full-length antibody recreated from the binder-1 scFv also exhibited specific binding. Conclusion: Our results establish the utility of using engrafted CDR3 sequences for selecting phage that recognize the idiotype of B-cell tumors.